AB0665 Usefulness of the ocular surface disease index (OSDI) in the assessment of vision-targeted health related quality of life (VT-HRQ) in patients with primary sjÖgren's syndrome. (23rd January 2014) - Ferro, F.; Baldini, C.; Gabbriellini, G.; Pepe, P.; Varanini, V.; Luciano, N.; Fannucchi, F.; Tavoni, A.; Nardi, M.; Bombardieri, S.
Abstract : Background: Assessment of quality of life in primary Sjögren's syndrome (pSS) has been generally performed employing generic measures of well-being, psycological distress, and fatigue without ocular dimensions. Objectives: (i) to assess vision-targeted health related quality of life (VT-HRQ) in patients with pSS in comparison to patients with different causes of dry eye using a dry-eye-disease specific instrument; (ii) to examine the association between VT-HRQ and ocular surface parameters in pSS focusing on patients' perception of symptoms, Schirmer's test, tear breakup time (TBUT), lissamine green staining (LGS) and artificial tear usage. Methods: Consecutive patients fulfilling the AECG criteria for pSS (mean age ±SD =56±14 yrs; mean disease duration ±SD =4.2±4.6 yrs) underwent Schirmer's testing without anesthesia, TBUT and LGS. Sex and age matched subjects with non-autoimmune dry-eye-disease were enrolled as controls. Subjects were administered the Ocular Surface Disease Index (OSDI), a 12-item questionnaire articulated in three subscales for the assessment of symptoms related to dry eye disease vision-related function, environmental triggers and their effect on vision. Patients' perception of symptoms was also assessed by VAS for dry mouth, dry eye, fatigue and pain. The ESSDAI was calculated in order to evaluate pSS activity. Patients' clinical, serological and histological features were also recorded. Spearman's rho, chi square and ANOVA-test were used for statistical analysis. Results: Thirty-six pSS female (mean age ±SD =56±14 yrs; mean disease duration ±SD =4.2±4.6 yrs) and 28 controls were enrolled in the study. According to the OSDI questionnaire, a "normal" score (0-12) was detected in 5/64 (13.9%) pSS patients and in 6/28 (21.4%) controls, a "mild" severity score (13-22) in 6/64 (16.7%) pSS patients vs 3/28 (10.7%) controls, a "moderate" score (23-32) in 6/64 (16.7%) pSS patients vs 6/28 (21.4%) controls, and a severe dry eye (33-100) in 19/64 (52.8%) pSS patients vs 13/28 (46.4%) controls, respectively. Overall, no differences were found in the OSDI score between pSS and non-autoimmune dry eye patients. Correlations between conventional objective measures of dry eye and OSDI/VT-HRQ were acceptable for GLS and TBUT (r=-0.53), but not statistically significant for Schirmer's test (r=-0.19). The strongest associations of the questionnaire was for patients' ocular (r=0.67) and fatigue VAS (r=0.52). A statistically significant correlation was also found between OSDI and artificial tear usage (p=0.003). No correlations were found between OSDI and patients' age, menopausal status, concomitant thyroiditis, ESSDAI score or positivity for antinuclear antibodies, anti-Ro/SSA, anti-La/SSB and Rheumatoid Factor. Conclusions: The OSDI is a useful instrument to assess quality of life in patients with dry eye disease; given its strong association with patients' perception of symptoms OSDI might be considered as an useful end point in pSS clinical trials. Disclosure of Interest: None Declared